Remote and Selective Control of Astrocytes by Magnetomechanical Stimulation (Adv. Sci. 6/2022). Issue 6 (24th February 2022) - Yu, Yichao; Payne, Christopher; Marina, Nephtali; Korsak, Alla; Southern, Paul; García‐Prieto, Ana; Christie, Isabel N.; Baker, Rebecca R.; Fisher, Elizabeth M. C.; Wells, Jack A.; Kalber, Tammy L.; Pankhurst, Quentin A.; et al.
Abstract : Magnetomechanical Stimulation Magnetomechanical stimulation enables remote and selective control of brain cell activity without any need for genetic modification. Antibody‐functionalized magnetic particles are targeted to the mechanosensitive astrocytes and a magnetic field is applied to activate signaling pathways that regulate a wide range of brain functions. More details can be found in article number 2104194 by Yichao Yu, Mark F. Lythgoe, and co‐workers.